2019
DOI: 10.3934/dcds.2019216
|View full text |Cite
|
Sign up to set email alerts
|

Topological characteristic factors along cubes of minimal systems

Abstract: In this paper we study the topological characteristic factors along cubes of minimal systems. It is shown that up to proximal extensions the pronilfactors are the topological characteristic factors along cubes of minimal systems. In particular, for a distal minimal system, the maximal (d − 1)-step pro-nilfactor is the topological cubic characteristic factor of order d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It is a long open question whether for a minimal distal system in Glasner's theorem in [17] one can replace the largest class d distal factor by the maximal pro-nilfactor of order d. Indeed, this is the case where we consider characteristic factors along cubes of minimal systems. In [6], the topological characteristic factors along cubes of minimal systems are studied. It is shown that up to proximal extensions the pro-nilfactors are the topological characteristic factors along cubes of minimal systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a long open question whether for a minimal distal system in Glasner's theorem in [17] one can replace the largest class d distal factor by the maximal pro-nilfactor of order d. Indeed, this is the case where we consider characteristic factors along cubes of minimal systems. In [6], the topological characteristic factors along cubes of minimal systems are studied. It is shown that up to proximal extensions the pro-nilfactors are the topological characteristic factors along cubes of minimal systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that up to proximal extensions the pro-nilfactors are the topological characteristic factors along cubes of minimal systems. In particular, for a distal minimal system, the maximal (d − 1)-step pro-nilfactor is the topological cubic characteristic factor of order d [6].…”
Section: Introductionmentioning
confidence: 99%
“…Up to an almost 1-1 modification, they showed that the topological characteristic factors are the pro-nilfactors (see [12, Theorem A]), which are the analogies in the ergodic situation. For other study on topological characteristic factors, see [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is a long open question whether for a minimal distal system in Glasner's theorem in [19] one can replace the largest class d distal factor by the maximal pro-nilfactor of order d. Indeed, this is the case when we consider characteristic factors along cubes of minimal systems. In [7], the topological characteristic factors along cubes of minimal systems are studied. It is shown that up to proximal extensions the pro-nilfactors are the topological characteristic factors along cubes of minimal systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that up to proximal extensions the pro-nilfactors are the topological characteristic factors along cubes of minimal systems. In particular, for a distal minimal system, the maximal (d − 1)-step pro-nilfactor is the topological cubic characteristic factor of order d [7].…”
Section: Introductionmentioning
confidence: 99%